2014
DOI: 10.1371/journal.pone.0109280
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Mortality Experiments with Juvenile Sea Bass (Dicentrarchus labrax) in Relation to Impulsive Sound Levels Caused by Pile Driving of Windmill Foundations

Abstract: Impact assessments of offshore wind farm installations and operations on the marine fauna are performed in many countries. Yet, only limited quantitative data on the physiological impact of impulsive sounds on (juvenile) fishes during pile driving of offshore wind farm foundations are available. Our current knowledge on fish injury and mortality due to pile driving is mainly based on laboratory experiments, in which high-intensity pile driving sounds are generated inside acoustic chambers. To validate these la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Significant effects of pile driving noise on oxygen consumption and grouping behavior have been mostly detected on confined individuals following exposure to the "real" pile driving noise in the natural environment (Santulli et al, 1999;Bruintjes et al, 2016a;Debusschere et al, 2016;Hawkins et al, 2014). On the contrary, the studies where no effect has been observed used playbacks records of real noises emitted either in aquaria or in the field (Bolle et al, 2012;Debusschere et al, 2014;Bruintjes et al, 2016b;Radford et al, 2016). The two exceptions reviewed here are the case of European plaice directly exposed to the real pile driving noise, where no detectable effects on oxygen consumption have been reported (Bruintjes et al, 2016b), and the modification of structure and dynamics of shoals of European seabass reported in aquaria (Herbert-Read et al, 2017).…”
Section: Acute Mnpmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant effects of pile driving noise on oxygen consumption and grouping behavior have been mostly detected on confined individuals following exposure to the "real" pile driving noise in the natural environment (Santulli et al, 1999;Bruintjes et al, 2016a;Debusschere et al, 2016;Hawkins et al, 2014). On the contrary, the studies where no effect has been observed used playbacks records of real noises emitted either in aquaria or in the field (Bolle et al, 2012;Debusschere et al, 2014;Bruintjes et al, 2016b;Radford et al, 2016). The two exceptions reviewed here are the case of European plaice directly exposed to the real pile driving noise, where no detectable effects on oxygen consumption have been reported (Bruintjes et al, 2016b), and the modification of structure and dynamics of shoals of European seabass reported in aquaria (Herbert-Read et al, 2017).…”
Section: Acute Mnpmentioning
confidence: 99%
“…Swimming speed and depth / Kastelein et al,. (2007) Dicentrarchus labrax / Primary and secondary stress response Debusschere et al, (2014Debusschere et al, ( , 2016 Fish shoal behavior (cohesion, direction, coordination) / Herbert- Read et al, (2017) Startle response, swimming speed and depth and group cohesion / Neo et al, (2014) Swimming patterns / Neo et al, (2015) Swimming speed and depth / Neo et al, (2016) / Ventilation rate Radford et al, (2016) Startle response, swimming behavior Cortisol, glucose, lactate, AMP, ADP, ATP and cAMP Santulli et al, (1999) Swimming speed and depth / Kastelein et al,. (2007)…”
Section: Acutementioning
confidence: 99%
“…In fish species, experiments have been conducted using several methods of acoustic exposure including: (1) playbacks of recorded sounds (Smith et al, 2004;Wysocki et al, 2006;Radford, 2013, 2014), (2) real boat or ship passes (Sarà et al, 2007;Graham and Cooke, 2008;Jacobsen et al, 2014;Simpson et al, 2016), (3) seismic airguns (Engas et al, 1996;Popper et al, 2005;Miller and Cripps, 2013;Thompson et al, 2013), and (4) impact pile driving (Debusschere et al, 2014(Debusschere et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Dähne et al, 2013, Debusschere et al, 2014. Moreover, many elements will influence the sound intensity, amplitude and frequency structure of the sound during pile driving including the pile's physical quantities, hammer type, pile driving method, strike rate, water depth, and the substrate of the area the pile is being installed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation